Estudio del sistema de gestión de contenidos multipropósito Drupal para el desarrollo de aplicaciones web. Caso aplicativo: formulación de perfiles de proyectos en la asociación de juntas parroquiales de Tungurahua - Huilcapi Jiménez, Luis Euclides (2011)
At present the Internet has become a way of living, style and needs of people and businesses or enterprises, the Internet and the Web are the most important developments of our time. Nowadays, this technology is a part of our daily lives because these technologies like CMS (existing in the market), the study of Drupal Multipurpose Content Managemet System for Web application development was developed. In this study we checked the architecture, requirements, characteristics, organizational structure, installation, configuration and administration of Drupal. Drupal is a PHP-based platform using My SQL as a data base manager and the Apache web server on Linux or Windows, it works with templates that can be created from the beginning or can be downloaded from the Drupal website, in the same way, with the modules offered by Drupal, it facilitates the construction of the site and its adequate separation design and content, it has a friendly interface for the development of components and is the most complete for the administration.